INTERACTIVE MULTIMEDIA ON BASIS ARTICULATE STORYLINE AND MARITIME ORIENTED FOR PLANTAE TOPIC IN SENIOR HIGH SCHOOL - Laras Wadah Warahmah; Azza Nuzullah Putri; Nurul Asikin (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Raising of science and technology in education often used in learning process, one of which is the use of interactive multimedia. The development of maritime-oriented interactive multimedia is carried out to improve student understanding and increase learning outcomes, and also to increase number of existing instructional media. This study aims to develop interactive multimedia based on Articulate Storyline on Plantae topic maritime oriented for class X students in Senior High School. Development model uses Plomp (2013). This model has three stages; 1) preliminary research, 2) development or prototyping phase, and 3) assessment phase. The data collection technique were a questionnaire, test instrument, and interview. Based on research result, the overall validation results are 87.65% with a very valid category. The level of practicality in interactive multimedia based on teacher and student assessments obtained an overall score of 91.15%, very practical. The product is proven to improve student learning outcomes, seen from the results of the pre-test and post-test through N-gain test, which obtained a value of 0.77 with an increase in the effectiveness of the high category. The results of the N-gain score showed an increase from before to after learning with. It can be concluded that interactive multimedia based on Articulate Storyline on Plantae topic maritime oriented can be used in the learning of biology.